2013
DOI: 10.1136/annrheumdis-2013-203455
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies from long-lived ‘memory’ plasma cells of NZB/W mice drive immune complex nephritis

Abstract: ObjectivesWe have previously shown that both short- and long-lived plasma cells (PCs) significantly contribute to autoantibody production in NZB/W mice as a model of lupus nephritis. The aim of this study was to determine the role of autoreactive long-lived (memory) PCs refractory to immunosuppression and B cell depletion in the pathogenesis of systemic lupus erythematosus.MethodsSplenic CD138+ antibody-secreting cells (ASCs) from >6-month-old NZB/W mice with high titres of anti-dsDNA autoantibodies or from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 32 publications
(38 reference statements)
5
44
1
5
Order By: Relevance
“…24,25 Recently, Cheng et al demonstrated that bone marrow plasma cells continuously secreted anti-dsDNA antibodies and caused immune complex nephritis after they were transferred from NZB/W mice to Rag1À/À mice. 26 This result is consistent with the results of the present study, which showed that the increased percentage of plasma cells in the bone marrow of SLE patients correlated with increased antidsDNA antibody and serum complement levels, which are significantly associated with lupus nephritis. This indicates that increased numbers of plasma cells in the bone marrow may trigger lupus by secreting anti-dsDNA antibodies; this increases the formation of anti-dsDNA-containing immune complexes, which then activate the complement system.…”
Section: Discussionsupporting
confidence: 95%
“…24,25 Recently, Cheng et al demonstrated that bone marrow plasma cells continuously secreted anti-dsDNA antibodies and caused immune complex nephritis after they were transferred from NZB/W mice to Rag1À/À mice. 26 This result is consistent with the results of the present study, which showed that the increased percentage of plasma cells in the bone marrow of SLE patients correlated with increased antidsDNA antibody and serum complement levels, which are significantly associated with lupus nephritis. This indicates that increased numbers of plasma cells in the bone marrow may trigger lupus by secreting anti-dsDNA antibodies; this increases the formation of anti-dsDNA-containing immune complexes, which then activate the complement system.…”
Section: Discussionsupporting
confidence: 95%
“…Because the terminal differentiation of GC B cells results in plasma cells, 43 and memory B cells are CD180-positive, we deduced that the downregulation of CD180 may participate in the differentiation of B cells into plasma cells but not to memory B cells. Recently, Cheng et al 44 showed that the adoptive transfer of CD138 1 anti- body-secreting cells (ASCs) from the spleen of NZB/W mice into Rag1-deficient mice could result in elevated serum autoantibody levels, immune complex nephritis, and a reduced survival rate. Moreover, transplantation of lipogranulomas, which are rich in anti-RNP auto-ASCs, leads to auto-antibody production in recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Residual autoreactive PCs after anti-CD20 depletion could continuously secrete pathogenic autoantibodies and either contribute to the chronic condition or lead to reactivation of the disease (15,(36)(37)(38). To assess the impact of CD19 and CD20 mAbs on humoral immune responses, we measured the serum and CNS Ab levels after a single injection of the mAbs at day 7 after EAE induction (Fig.…”
Section: Cd19 Mab Surpasses Cd20 Mab In Inhibiting Pre-existing Ig Anmentioning
confidence: 99%